The role of fintech and green finance in fostering environmental sustainability: Evidence from the ASEAN-5 - Bakri, Muhammad Rafi; Prihadi, Tri Widodo Setiyo; Futri, Ulfa (Center for Science and Technology, IAIN Surakarta, 2025)
Environment and economy are frequently seen as opposing forces. For every government initiative to boost the economy, there is an equal and opposite measure to protect the environment. The overarching goal of this research is to provide empirical evidence of how green finance and fintech sway policymakers to reduce the economic-environmental trade-off. Secondary data from 2000–2023, together with a sample of ASEAN-5 nations, are used in this analysis. To determine the impact of the study's independent variables on environmental damage, quantitative approaches, particularly CS-ARDL, are employed. The study's findings suggest that the five ASEAN nations may lessen their environmental impact by utilizing green finance and fintech. The government, with the exception of Singapore, needs to move swiftly, since the expected decline is too sluggish. Among the ASEAN-5 nations, Singapore has the potential to do more to protect the environment than its peers.